Nation as a Specifically European Notion: Forming and Deforming Historical and Current Reality by a Word - Hroch, Miroslav (Dějiny – teorie – kritika, 2017)
The aim of this study is to demonstrate how globalisation effected certain changes in our understanding of the notions of nation and nationalism. First of all, I argue that a nation was formed as a specifically European phenomenon in the course of the process of modernisation. Positive connotations of the term ‘nation’ evolved in connection with specifically European intellectual movements starting with humanism, through Renaissance, and all the way to Enlightenment. The identification of individuals with their nations was then referred to as patriotism. Secondly, only once most European nations were fully formed, identification of individuals with their nations started being denoted by a newly invented term ‘nationalism’. Thirdly, in the course of the twentieth century, nationalism was integrated into the terminology of politics and social sciences, which then applied this concept not only to European nations but also new states which formed outside Europe and claimed to be nation-based. Fourthly, in consequence of this development, the content of the notion of nationalism was extended so as to include the identification of individuals with formations that significantly differed from European nations. And finally, since due to a sort of mindless habit of thought, the term nationalism started to be applied in this altered, globalised sense even to analyses of development of European nations in the nineteenth century, there is a distinct possibility that this may lead to a significant retrospect distortions of European history representations.